2022
DOI: 10.1186/s43014-022-00109-w
|View full text |Cite
|
Sign up to set email alerts
|

Brewing and biochemical characterization of Camellia japonica petal wine with comprehensive discussion on metabolomics

Abstract: A novel wine has been developed from Camellia japonica’s petal by fermenting the decoction with Saccharomyces cerevisiae or brewer’s yeast. pH, brix, specific gravity and alcohol percentage were tested to study the physicochemical properties of the wine. Qualitative tests indicated presence of phenols such as flavonoids, coumarins; protein; glycosides; glycerin; terpenoids; steroids; and fatty acids in the wine. Total phenol content was found high in the decoction and in its fermented form as well. In vitro bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The determination of total phenolic content (TPC) was carried out following the procedure outlined by Labar et al [18] and Majumder et al [19] . In this approach, sample extracts (100 μl) were placed in clean test tubes and allowed to incubate at room temperature for a duration of five minutes after the addition of 400 μl of 10% Folin-Ciacalteu reagent.…”
Section: Quantitative Biochemical Tests Total Phenol Contentmentioning
confidence: 99%
“…The determination of total phenolic content (TPC) was carried out following the procedure outlined by Labar et al [18] and Majumder et al [19] . In this approach, sample extracts (100 μl) were placed in clean test tubes and allowed to incubate at room temperature for a duration of five minutes after the addition of 400 μl of 10% Folin-Ciacalteu reagent.…”
Section: Quantitative Biochemical Tests Total Phenol Contentmentioning
confidence: 99%
“…Specific gravity (Sg) of the fermented samples were determined mathematically by calculating the ratio of the specific weight of sample to the specific weight of water at 4°C. Alcohol percentage or %ABV in fermented samples (GW and GR) were calculated by entering OG (original gravity or specific gravity of RFD) and FG (final gravity or specific of fermented beverages) values into an online ABV calculator (11,16,24). Experiments were carried out in triplicates and results were expressed as mean ± SD (n=3).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…The mixture was left in dark for sixty minutes, and absorbance was measured at 650 nm in a UV-vis spectrophotometer (Cary-60, Agilent). TPC was measured against gallic acid standard curve (R² = 0.9975; y = 0.0043x -0.1672) and results were expressed as gallic acid equivalent (mg GAE/100 mL) (16). The data were expressed as means of three replicates ± Standard Deviation (SD).…”
Section: Quantification Of Tpc (Total Phenol Content)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers have used metabolomics techniques to analyze and characterize in detail the major metabolites of the genus Camellia . For example, metabolomics analysis of Camellia japonica has been 12 revealed that its flowers contain high amounts of kaempferol, which have a strong antioxidant and anti-inflammatory effect and should be an important source for the production of natural health products and medicines. Metabolomics of Camellia oleifera 13 showed that it is rich in unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid, which have important health effects on human health and whose applications are gaining increasing attention.…”
Section: Introductionmentioning
confidence: 99%